Perlindungan Hukum Terhadap Konsumen Atas Pemberian Keterangan Yang Menyesatkan Oleh Pelaku Usaha Digital Ditinjau Dari Aspek Pidana - Denny Prasetyo; Maleman sura anabertha sembiring (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
Providing information through advertisements offered by business actors has the potential to mislead consumers because it is not in accordance with the facts. Several cases have occurred and potentially violate Law No. 8 of 1999 on Consumer Protection (UUPK) as well as violations in the Criminal aspect. The case presented in this research is Ludmilla Arief vs PT Nissan Motor Indonesia (PT NMI). The advertisement containing misleading information published by PT NMI encouraged Ludmilla to buy a Nissan March car. The advertisement conveyed that the Nissan March had the advantage of being fuel-efficient, but in reality, this was not the case. Ludmilla filed a lawsuit against PT NMI at the Jakarta Consumer Dispute Settlement Board (BPSK) for disseminating misleading advertisements. BPSK granted the lawsuit, but PT NMI objected and the case reached the Supreme Court. The research questions are: how is consumer protection under Law No. 8 of 1999 on Consumer Protection?; and what are the criminal sanctions based on Law No. 8 of 1999 on Consumer Protection? This research uses a normative juridical approach, which focuses on examining the application of the principles or norms in positive law. The research findings show that this case involved a promise that the Nissan March car promoted as fuel-efficient at 18.5 km/liter, which encouraged consumer Ludmilla Arief to buy the car. However, this promise was not in line with the actual situation. Viewed from the characteristics of misrepresentation conducted by the business actor, this action qualifies as misrepresentation done deliberately to mislead consumers (fraudulent misrepresentation).